Shale fault zone structure and stress dependent anisotropic permeability and seismic velocity properties (Opalinus Clay, Switzerland). (March 2021) - Wenning, Quinn C.; Madonna, Claudio; Zappone, Alba; Grab, Melchior; Rinaldi, Antonio P.; Plötze, Michael; Nussbaum, Christophe; Giardini, Domenico; Wiemer, Stefan
Abstract: Given shale's potential to serve as both a caprock for geological carbon sequestration and as the host for nuclear waste disposal, this study focuses on the structural characterization around a 1.5–3 m thick fault within the Opalinus Clay host rock and petrophysical characterization of both the host rock and fault core. Seven boreholes were drilled at the Mont Terri Rock laboratory in late 2018 to constrain the orientation of the so-called 'Main Fault' and several fracture families within the fault core using core and image logs. Contrary to typical fault models, matrix permeability and seismic velocity measurements show similarities in the host rock and within the Main Fault. In the clay-rich samples, measurements performed in laboratory at varying confining pressures indicate p-wave velocities range from 2.60 to 2.95 km/s perpendicular to foliation and 3.38–3.58 km/s parallel to foliation at near in-situ confining pressures, which increase with similar anisotropy at higher confining pressures (200 MPa). Since the permeability of the host rock and fault zone is very low (10 −19 –10 −21  m 2 ) flow is expected to prevail along fractures, where critical stress fault analysis suggests that potential hydraulically conductive fractures are actually conjugate to the Main Fault trend. Key points: Borehole image logs reveal a complex internal fault structure. Seismic velocities and permeability of the host shale and faulted shale are similar. With respect to the current state of stress, the main fault planes are less prone for reactivation than conjugate fractures.